(untitled) (Itinera, 2024)
The aim of this paper is to explore some existential possibilities that the concept of mimesis has in Kierkegaard. To this end, mimesis will be analyzed in two moments of his: in the life of the aesthete in Either-Or, where mimesis is related to the notions of poetry and fantasy, and in relation to the figures of the lily in the field and the bird in the sky. Two different notions of mimesis will then be studied in their dialectic between introspection and alienation. The aesthetic stage of mimesis will reveal the paradox of aesthetic life: on the one hand, the aesthete is apparently introflected, living in a world constructed of mimetic phantasms in his own image, but on the other hand, trapped in these reflections, he is unable to grasp his own self as a real possibility and is thus hopelessly alienated from himself. The opposite happens in the religious stage of mimesis, in which it is revealed that only in the apparent extroversion of imitating the absolute other is it possible to grasp one’s own self.